Single-Step Full-Face Surgical Treatment of the Facial Profile - Bertossi, Dario; Sacchetto, Luca; Chirumbolo, Salvatore; Panozzo, Giorgio; Kapoor, Krishan Mohan (Facial Plastic Surgery, 2023)
The present study was performed to describe how much affordable, feasible, and straightforward is the approach the authors called “single-stage full-face surgical profileplasty,” tailored to greatly improve the surgery of the facial profiling setting and achieve complete profile correction at the same time. From January 2010 to May 2019, 113 patients (95 females and 18 males; aged 19 − 63 years) were surgically treated for full-face profile amelioration. Profile correction was performed by using a combination of five procedures out of other various previously experienced: forehead fat grafting, rhinoplasty, lip fat grafting, genioplasty, and submental liposuction. All patients were assessed at 1, 3, 6, and 12 months following surgery for assessing the surgical profile treatment (SPT) outcome and any possible side effects of the combined treatment. Facial profile stability at 1 year was taken as the completion point of this treatment. Arnett et al's “Soft Tissue Cephalometric Analysis” (1999) was used to clinically evaluate the soft tissues before and after the SPT. Patients' satisfaction was measured with the Client Satisfaction Questionnaire-8” at 3 and 12 months after surgery. Statistics were used for Arnett et al's evaluation. Almost all the values were consistent and reached the normal ranges indicated by Arnett et al (p < 0.001), confirming that the desired results of the surgical profileplasty have been achieved. Single-stage full-face surgical profile treatment helps in correcting faults of the global facial deformity, in every single treated area, providing an overall improvement in facial aesthetics and harmony. Obtaining the simultaneous correction in the whole face has also the advantage of avoiding multiple surgical procedures, reducing postoperative discomfort, and the overall risks for the patient due to multiple surgical and anesthetic procedures.
Keywords: beauty; profileplasty; Arnett et al's cephalometric analysis; aesthetic surgery; facial harmony